P098 Anti-TNF biologic therapy does not increase postoperative morbidity in pediatric Crohn's patients. (July 2019) - Ahmad, Alsughayer; Nicholas, McKenna; Edward, Loftus; Laura, Raffals; William, Faubion; Amy, Lightner
Abstract : BACKGROUND: Limited knowledge exists as to what impact preoperative biologic therapy has on post-operative complications in pediatric patients undergoing abdominal surgery for Crohn's disease (CD). Therefore, we sought to determine the 30-day postoperative infectious complication rate among pediatric CD patients who received biologic therapy within 12 weeks of an abdominal operation. METHODS: A retrospective chart review was performed on pediatric (<18 years of age) CD patients who underwent an abdominal operation between 1/1/2008 and 12/31/2017. Patients were grouped according to whether they received an anti-TNF (infliximab, adalimumab, certolizumab pegol) or no biologic therapy within 12 weeks prior to the operation. The primary outcome was a the overall 30-day postoperative infectious complication rate. Secondary outcomes included 30-day readmission rate and return to the operating room (ROR). RESULTS: A total of 69 pediatric CD patients met inclusion criteria (n = 54 anti-TNF therapy, n = 15 received no biologic therapy). There were no differences between the anti-TNF and no biologic cohorts with respect to demographics or CD characteristics. No significant differences in overall 30-day postoperative infectious complications existed between patients exposed to anti-TNF agents and those with no preoperative exposure, or in its subcategories of surgical infectious complications and non-surgical infectious complications. There was also no difference in the rate of ileus, readmission, or ROR. CONCLUSION(S): Preoperative exposure to anti-TNF biologic therapy does not add to overall or infectious 30-day postoperative morbidity in pediatric CD patients.